Spécial Guyane - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Le Centre Technique Forestier Tropical consacre deux numéros spéciaux de sa collection Bois et Forêts des Tropiques